2015
DOI: 10.15252/embj.201490174
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y regulates the hematopoietic stem cell microenvironment and prevents nerve injury in the bone marrow

Abstract: Many reports have revealed the importance of the sympathetic nervous system (SNS) in the control of the bone marrow environment. However, the specific role of neuropeptide Y (NPY) in this process has not been systematically studied. Here we show that NPY-deficient mice have significantly reduced hematopoietic stem cell (HSC) numbers and impaired regeneration in bone marrow due to apoptotic destruction of SNS fibers and/or endothelial cells. Furthermore, pharmacological elevation of NPY prevented bone marrow im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 49 publications
(68 reference statements)
2
71
0
Order By: Relevance
“…This finding suggests a putative role for NPYR1 activation by NPY, resulting in the promotion of microvascular proliferation characteristic of the proliferative phase of IHs, although conclusive evidence for this remains a topic of further investigation. NPY-deficient mice have been shown to exhibit a significantly reduced number of haematopoietic stem cells, as well as impaired regeneration in bone marrow due to apoptotic destruction of sympathetic nervous system fibres and/or endothelial cells (13). Taken together, this suggests that the reduction in NPYR1 + cells during involution demonstrated in this study may, in part, explain the observed increased apoptosis evident in involuted IHs (14).…”
Section: Discussionsupporting
confidence: 59%
“…This finding suggests a putative role for NPYR1 activation by NPY, resulting in the promotion of microvascular proliferation characteristic of the proliferative phase of IHs, although conclusive evidence for this remains a topic of further investigation. NPY-deficient mice have been shown to exhibit a significantly reduced number of haematopoietic stem cells, as well as impaired regeneration in bone marrow due to apoptotic destruction of sympathetic nervous system fibres and/or endothelial cells (13). Taken together, this suggests that the reduction in NPYR1 + cells during involution demonstrated in this study may, in part, explain the observed increased apoptosis evident in involuted IHs (14).…”
Section: Discussionsupporting
confidence: 59%
“…A systematic search of protein sequence databases for proteins containing putative CD26 recognition sites intriguingly identified the neurotransmitter NPY (26), a ligand with cognate receptors on monocytes, osteoblasts, stromal cells, and ECs and that has been shown to regulate immune cell and bone homeostasis (27)(28)(29)(30). In addition, recent studies suggest a role for NPY in the regulation of BM niche components and HSPC trafficking (31,32). To test the potential role of CD26-cleaved NPY in regulating HPSC trafficking in response to G-CSF, we first validated by mass spectrometry that CD26 cleaved NPY to the expected truncated NPY 3-36 form ( Figure 5A).…”
Section: G-csf Increases Ec Cd26 and Enhances Hspc Transendothelial Mmentioning
confidence: 98%
“…Furthermore, pharmacological elevation of neuropeptide Y prevented the deficits, while neuropeptide Y injection into mice lacking the Y1 receptor specifically in macrophages did not rescue BM dysfunction. 188 …”
Section: Heterogeneity Of Cells Of the Nichementioning
confidence: 99%